Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Financial Distress dengan Struktur Modal Sebagai Variabel Moderasi ( Pada Perusahaan Food & Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - angreini, Duwita; Rinofah, Risal; Sari, Pristin Prima (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the effect of profitability, liquidity, and leverage on financial distress with capital structure as a moderating variable in Food & Beverage companies listed on the IDX during 2021–2024. A quantitative approach was used with secondary data and moderated regression analysis. The results show that profitability has no significant effect, while liquidity and leverage significantly affect financial distress. Capital structure moderates the effects of liquidity and leverage but not profitability. The study implies that companies should manage their capital structure wisely to minimize the risk of financial distress.